HUBUNGAN KARAKTER KERJA KERAS DENGAN KEMAMPUAN LITERASI SAINS SISWA KELAS V SDN 12 SINGKAWANG - Murdani, Eka; Iwan, Iwan; Sumarli, Sumarli; Mertika, Mertika (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to determine the hard-working character of fifth-grade students at SDN 12 Singkawang and to examine their scientific literacy skills. It also aims to identify the relationship between the hard-working character and scientific literacy skills of fifth-grade students at SDN 12 Singkawang. This research employed a quantitative approach with a descriptive method and an associative correlational research design. The population of this study consisted of all fifth-grade students, divided into two classes, VA and VB, totaling 60 students. The sampling technique used was saturated sampling. The data collection instruments were questionnaires and essay tests. The data were analyzed using descriptive statistical analysis and correlation analysis. The results showed that the average score of the students’ hard-working character was 67.23, which falls into the “good” category. Meanwhile, the average score of students’ scientific literacy skills was 80, categorized as “high.” The correlation analysis revealed a significant relationship between the hard-working character and the scientific literacy skills of fifth-grade students at SDN 12 Singkawang, with a determinant coefficient of 17.64% and a t-value of 3.516, which is greater than the t-table value of 2.002.